Study for Comparison of CD40-mAb and CD40L-Ab Costimulation Blockade after Life-Supporting Orthotopic Cardiac Xenotransplantation of Multi-Transgenic Pig Hearts into Baboons with a Worldwide First Successful Long-Term Survival. (July 2018) - Brenner, Paolo; Reichart, Bruno; Mayr, Tanja; Längin, Matthias; Güthoff, Sonja; Buchholz, Stefan; Michel, Sebastian; Lutzmann, Isabelle; Werner, Fabian; Bauer, Andreas; Klymiuk, Nikolai; Wolf, Eckhard; et al.
Abstract : Objectives: Life-supporting orthotopic cardiac xenotransplantations (OHXTx) in a pig-to-baboon model with GalT-KO/hCD46/hTM transgenic donor pigs were performed with a compatible, non-toxic immunosuppression (IS) based on CD40mAb co-stimulation blockade in group G1 and in a group G2 with a new pasylated, non-thrombogenic CD40L-Ab. Chemical procedure of PASylation prolongs plasma half-life by 170-fold to several days. Primary aims were to realize a constant preclinical long-term survival in a life-supporting cardiac xenotransplantation model and to prevent perioperative cardiac xenograft dysfunction (PCXD) as a kind of cardiac low output. Methods: OHXTx according to the technique of Lower and Shumway were performed in 11 baboons with transgenic pig hearts. The new IS consisted of a recombinant mouse-rhesus chimeric CD40 (clone 2C10R4) antibody in G1 (n=7) or a PASylated Fab-CD40L antibody (XL-protein/Wacker-Chemie) in G2 (n=4) combined with ATG, rituximab, MMF (no tacrolimus or cyclosporine!) and steroids. Results: Survival in G1 with CD40mAb were 3, 1, 30, 1, 1** and 27 day(s) with 2 cases of PCXD. Using CD40L-Ab in G2 PCXD was observed in 1 case and the recipients survived 1, 18 and 40 days. Ischemic time of the hearts ranged from 112-128 min. Primary cause of death mostly were renal and hepatic failure, one died of a neurological deficit**, another after hematothorax, but no hyperacute or delayed xenograft rejection occurred. After several weeks a pig donor organ (over)growth was found. All long-term surviving baboons were in good general conditions until to the last days. Mean survival in G1 (CD40Ab) was 10.5+/-4.90 days and in G2 (Fab-CD40L) 19.7+/-7.84 days and without PCXD and brain damage** 20+/-6.55 days in G1 and 29+/-7.78 days in G2. In a preliminary modified subgroup (unpublished data und matter of a patent) one baboon with CD40L-Ab survived 50 days and another baboon (B67 with CD40Ab) reached and was successfully terminated at the endpoint of study on day 90 with no signs of rejection of the xenograft. Conclusion: Co-stimulation blockade with CD40L antibody tended to prolong survival time after orthotopic cardiac xenotransplantation, but with so far incomplete groups statistically not significant. In total survival in this important life-supporting orthotopic model was significantly prolonged with a less toxic IS and better quality of life. This is an important milestone and progress on the way to a long-term survival of 2 -3 months, which is necessary for first clinical cardiac xenotransplantations. This aim was now first time worldwide reached with our last 90-days surviving baboon B67 in the last subgroup and must be replicated another 5 times before starting a clinical study.